The influence of organizational culture and work environment on performance at UD. Kariasih Mengwi Badung - Made Mulyadi; Ni Kadek Ayu Rasita Dewi; I Nyoman Rasmen Adi; Luh Gede Elvina Adi Saputri (Institute of Computer Science (IOCS), 2023)
This research was motivated by the importance of human resource involvement at UD. Kariasih Mengwi Badung in achieving UD's goals. Kariasih Mengwi Badung. The purpose of this study was to determine the effect of organizational culture and work environment on employee performance both partially and simultaneously. This research was conducted at UD. Kariasih Mengwi Badung with a population of 40 employees. This study uses the census technique so that all members of the population are involved as research subjects. Primary data collection was carried out using a questionnaire. Hypothesis testing is done using multiple linear regression analysis. Based on the results of the analysis it can be concluded that: 1) Organizational culture has a positive and significant effect on employee performance as evidenced by tcount (3.121) > ttable (2.026) sig. 0.003 < α 0.05 so Ho is rejected and H1 is accepted, 2) The work environment has a positive and significant effect on employee performance as evidenced by the tcount (4,249) > ttable (2,026) sig. 0.000 < α 0.05 so Ho is rejected and H2 is accepted, 3) Organizational culture and work environment have a positive and significant effect on employee performance as evidenced by Fcount (14,526) > Ftable (3,26) and sig 0.000> 0.05 so that Ho is rejected and H3 is accepted and concluded the results of research at UD. Kariasih Mengwi Badung is as follows organizational culture has a positive and significant effect on employee performance at UD. Kariasih Mengwi Badung.